2020
DOI: 10.21608/aimj.2020.35322.1278
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of virulence factors and antifungal susceptibility of Candida species isolated from catheter associated urinary tract infections

Abstract: Background: Catheter associated urinary tract infection (CAUTI) is a crucial attribute to virulence of organisms. Emergency of non albicans Candida (NAC) species become common due to several virulence factors, which play an important role in pathogenicity and their resistance to treatment. Aim of the work: To investigate different virulence factors of Candida spp. isolated from CAUTI patients and evaluate their antifungal susceptibility. Patients and Methods: Urine samples collected from 219 indwelling cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Older age is a classical risk factor for candiduria due to the attenuated host defense mechanisms in this age group. These findings coincide with reports of other studies as Ismail and colleagues in Cairo, Egypt confirmed positive candiduria in patients whose ages were between 50-70 years with predominance of female gender 64 % [16]. Also, Jiménez-Guerra et al and Melges et al found that the average age of patients with candiduria was 65 and 63 years, respectively [23,24].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Older age is a classical risk factor for candiduria due to the attenuated host defense mechanisms in this age group. These findings coincide with reports of other studies as Ismail and colleagues in Cairo, Egypt confirmed positive candiduria in patients whose ages were between 50-70 years with predominance of female gender 64 % [16]. Also, Jiménez-Guerra et al and Melges et al found that the average age of patients with candiduria was 65 and 63 years, respectively [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…isolates (61.1%) were from patients admitted in ICU with prolonged antibiotic intake. Our results are supported by Ismail et al, Chandak et al and Melges et al who reported that 78 %, 89.2% and 100 %, respectively of all positive candiduria patients were on antibiotic treatment [16,21,24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The widespread and prolonged use of conventional antimicrobial agents has led to the emergence of fungal drug fights ( Abdel-Shafi et al., 2020 ; Enan et al., 2020 ; Judan Cruz et al., 2021 ). Researchers are now exploring innovative strategies to combat multidrug-resistant microbial strains, including the use of nanomaterials ( El-Gazzar and Ismail, 2020 ; Ismail et al., 2020a ; Sitohy et al., 2021 ) and probiotics ( Osman and El-Gazzar, 2021 ), as the development of new antibiotics is challenging.…”
Section: Introductionmentioning
confidence: 99%